Bacterial dynamics in spring water of alpine karst aquifers indicates the presence of stable autochthonous microbial endokarst communities - Andreas H. Farnleitner; Ines Wilhartitz; Gabriela Ryzinska; Alexander K. T. Kirschner; Hermann Stadler; Martina M. Burtscher; Romana Hornek; Ulrich Szewzyk; Gerhard Herndl; Robert L. Mach (Environmental Microbiology, 2005)
Summary Spring water of two alpine karst aquifers differing in hydrogeology but of nearby catchments were investigated for their bacterial population dynamics. Dolomite karst aquifer spring 1 (DKAS 1) represents a dolomitic‐limestone karst aquifer spring showing high average water residence time and relative constant flow. Limestone karst aquifer spring 2 (LKAS 2) constitutes a typical limestone karst aquifer spring with a dynamic hydrological regime and discharge. Dolomite karst aquifer spring 1 yielded constantly lower cell counts and biomasses (median of 15 × 10 6 cells l −1 and 0.22 µg C l −1 ) as the LKAS 2 (median of 63 × 10 6 cells l −1 and 1.1 µg C l −1 ) and distribution of morphotypes and mean cell volumes was also different between the considered systems, indicating the influence of hydrogeology on microbial spring water quality. Molecular bacterial V3 16S‐rDNA profiles revealed remarkable constancy within each spring water throughout the investigation period. Time course analysis of a flood event in LKAS 2 further supported the trend of the temporal constancy of the microbial community. Except for one case, retrieval of partial and full length 16S rDNA gene sequences from the relative constant DKAS 1 revealed similarities to presently known sequences between 80% to 96%, supporting the discreteness of the microbial populations. The gathered results provide first evidence for the presence of autochthonous microbial endokarst communities (AMEC). Recovery of AMEC may be considered of relevance for the understanding of alpine karst aquifer biogeochemistry and ecology, which is of interest as many alpine and mountainous karst springs are important water resources throughout the world.